CRAFTING AN INTERACTIVE VIDEO GAME COURT SYSTEM FOR MORAL DEVELOPMENT AND LEGAL INSIGHT - Wibowo, Tony; Adnas, Diny Anggriani; Mulyanto, Mulyanto; Marvel, Alberta Adeline (ZONAsi: Jurnal Sistem Informasi, 2025)
This paper explores the use of the Game Development Life Cycle (GDLC) in creating a hybrid game that integrates visual novel storytelling with match-three puzzle mechanics. The visual novel emphasizes player decision-making and narrative immersion, while the puzzle element adds strategic challenges that propel the story. GDLC's structured phases facilitated efficient teamwork, resource management, and iterative testing throughout development. The findings highlight GDLC's effectiveness in merging diverse game genres, creating an engaging experience for varied audiences. Given the declining popularity of standalone puzzle games, this approach demonstrates how puzzle mechanics can enhance broader gameplay structures, enriching narrative flow and player engagement. The study also examines the challenges of combining visual novels and puzzles, alongside cultural considerations for addressing societal issues in Indonesia. This research underscores GDLC's potential for cross-genre innovation and invites future exploration into player-driven narratives and dynamic content in game design.